2022
DOI: 10.1021/acs.energyfuels.2c00912
|View full text |Cite
|
Sign up to set email alerts
|

Improved the Electrocatalytic Hydrogen Evolution Performances of Co-MOF Derivatives Through Introducing Zinc Ions by Two Ways

Abstract: Due to the high price and rareness of precious metal electrocatalysts, the preparation of cheap, high-efficiency nonprecious metal electrocatalysts is urgently needed. In this paper, a Co-metal-organic framework (MOF) has been synthesized by the hydrothermal method. In view of the poor electrocatalytic performance of pristine Co-MOF, we used it as a template and obtained the Co-MOF-800 electrocatalyst by high-temperature calcination at 800 °C under a nitrogen atmosphere. To further improve the electrocatalytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…32 Therefore, we further investigated the field emission transmission electron microscopy (TEM) of Zn/Co-bza-800 and Zn-bza@Co-800, and it can be seen from Figure 5a,b that the metal nanoparticles are uniformly distributed and all wrapped by the carbon; the lattice stripes 0.196 nm corresponded to the Co(111) crystal plane in Zn/Co-bza-800 (Figure 5c) and 0.219 nm corresponded to the Co(111) crystal plane in Znbza@Co-800 (Figure 5d). 33 We found that the crystal plane spacing is different in Zn/Co-bza-800 and Zn-bza@Co-800. 34 Figure 5e shows the distribution of Zn, Co, C, N, and O elements, which also proves the introduction of Co.…”
Section: Scanning Electron Microscopy and Transmission Electron Micro...mentioning
confidence: 71%
See 1 more Smart Citation
“…32 Therefore, we further investigated the field emission transmission electron microscopy (TEM) of Zn/Co-bza-800 and Zn-bza@Co-800, and it can be seen from Figure 5a,b that the metal nanoparticles are uniformly distributed and all wrapped by the carbon; the lattice stripes 0.196 nm corresponded to the Co(111) crystal plane in Zn/Co-bza-800 (Figure 5c) and 0.219 nm corresponded to the Co(111) crystal plane in Znbza@Co-800 (Figure 5d). 33 We found that the crystal plane spacing is different in Zn/Co-bza-800 and Zn-bza@Co-800. 34 Figure 5e shows the distribution of Zn, Co, C, N, and O elements, which also proves the introduction of Co.…”
Section: Scanning Electron Microscopy and Transmission Electron Micro...mentioning
confidence: 71%
“…Among them, the structures of Zn/Co-bza-800 and Zn-bza@Co-800 are rougher than that of Zn-bza-800 as can be seen from Figure d,e, indicating that Zn/Co-bza-800 and Zn-bza@Co-800 may provide more active sites than Zn-bza-800 . Therefore, we further investigated the field emission transmission electron microscopy (TEM) of Zn/Co-bza-800 and Zn-bza@Co-800, and it can be seen from Figure a,b that the metal nanoparticles are uniformly distributed and all wrapped by the carbon; the lattice stripes 0.196 nm corresponded to the Co(111) crystal plane in Zn/Co-bza-800 (Figure c) and 0.219 nm corresponded to the Co(111) crystal plane in Zn-bza@Co-800 (Figure d) . We found that the crystal plane spacing is different in Zn/Co-bza-800 and Zn-bza@Co-800 …”
Section: Resultsmentioning
confidence: 97%
“…Due to its vast surface area, tunable porosity and ability to adapt to various metal centers and ligands, MOFs are regarded as promising electrocatalytic materials. 3,4 The distance that charge carriers must travel to reach the reactants can be greatly reduced when using MOFs with high porosity and accessible surface area in electrocatalysis. To increase both chemical and thermal stability, an organic ligand must covalently bind with different metal ions.…”
Section: Introductionmentioning
confidence: 99%
“…2,7 To overcome this and to achieve the optimal performance, conductive materials are commonly composited in the MOF derivatives/compositions. 4,5,8 Another strategy is to carbonize the pristine MOFs at a temperature of 500 1C under an inert atmosphere in order to generate MOF-based carbon composites to produce heteroatom-doped porous carbons decorated with metal/metal oxide nanoparticles. In this aspect, it is expected that the carbonized MOFs perform better than the pristine MOF materials.…”
Section: Introductionmentioning
confidence: 99%
“…Transition metals, especially Ni and its oxides, have been considered as the research topic of non-noble HER cocatalysts due to their abundance, low cost, easy preparation, chemical stability, and high efficiency for HER. Generally, the cocatalysts are incorporated into some substrates such as graphitic carbon nitride and various carbon nanomaterials, which benefit for regulating the structure and morphology of cocatalysts and improving the catalytic activity. For instance, Lu et al reported the NiS x cocatalyst decorated on the graphene (NiS x /G) nanohybrid that exhibited the efficient dye-sensitized photocatalytic HER activity .…”
Section: Introductionmentioning
confidence: 99%